Study and Analysis of Various Existing Techniques for the Load Balancing in Cloud Computing Environment - et al., Sanjiv Kumar Grewal (International Journal of Advanced Science and Technology, 2020)
Cloud computing is the technology that uses the internet to store data and applications. Various issues and challenges in cloud computing are load balancing, fault tolerance, availability, Virtual Machine (VM) relocation etc that needs to be deal with. But, the main challenge is load balancing of resources. Load balancing techniques are used to equally distribute the resources among all nodes in distributed system and it will help in reducing the response time. In this paper, several static and dynamic load balancing approaches under different categories are discussed also compare each algorithm using some performance parameter.